STUDI PERBANDINGAN STRESS RATIO PADA PORTAL BAJA MENGGUNAKAN BRACING DENGAN EFFECTIVE LENGTH METHOD (ELM) DAN DIRECT ANALISYS METHOD (DAM) - Cut M. Rani; Muttaqin Muttaqin; Teuku Budi Aulia (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2019)
In the design of high and low-rise buildings, structural systems should consider the requirements of strength, stifness, and stability. The addition of bracing affects the stiffness of the structure of the building. In SNI 03-1729-2002 there is an Effective Length Method (ELM) method which only recommends first-order analysis with amplification factor. However, currently there is a new structural design regulation that is SNI 1729: 2015 which refers to the American Institute of Steel Contruction (AISC 2010) where the steel structure stability planning has taken into account the second-order effect directly. This study aims to compare the application of Direct Analysis Method (DAM) and Effective Length Method (ELM) on 2D simple structure, where the comparison of both methods is focused on stress ratio value, which aims to determine more effective and efficient method in designing of braced steel frame structure. The difference values of stress ratio obtained in this study varies from 0.1 to 8.9%, where the value of DAM stress ratio is smaller than ELM. Comparison between the two methods shows that DAM is a more effective method and results in higher profile capacity than ELM.